Peculiarities of nurses work for nursing patients with chronic leg ulcers - Čerkauskaitė, Sonata; Česnauskienė, Audronė (Slauga. Mokslas ir praktika, 2022)
Legs ulcers are one of the most difficult Problem to solve in modern medicine. Although a wide variety of drugs and mechanical methods have been developed to treat ulcers, no marked improvement has yet been discovered in either wound healing or the social status of patients. Leg ulcers are not only a common, difficult to treat, but also economically unprofitable health condition requiring a lot of care, work and knowledge. Study aim – to evaluate peculiarities of nurses work for nursing patients with chronic leg ulcers. Study methods. Quantitative research method using an anonymous questionnaire for nurses caring for patients with chronic leg ulcers. Descriptive statistics of results. Results. Nurses working in a hospital at least once a week care for patients with chronic leg ulcers, which are usually localized in the calf, foot, ankle areas. Patients with other comorbid conditions (e. g. diabetes, arterial hypertension and other) are needed specific nursing needs – longer wound healing, prevention of infections and bleeding, balanced diet and temperature control. Nursing patients with chronic leg ulcers the body position of the nurses mostly is forced, they work bent over. The work of nurses is most complicated by the lack of nursing assistants.